Interactive physiology for biology of humans concepts, applications, and issues - Goodenough, Judith; McGuire, Betty; Wallace, Robert A. (Benjamin Cummings, 2007)
IP for Human Biology is a browser-based tutorial program for Human Biology students. Seven modules contain topics common to Human Biology courses. Shockwave files load to display animations, tutorials, and quizzes.